Uniform Evaluation of Clinical Teaching – an instrument for specific feedback and cross comparison between Departments - Kihlberg, Pernilla; Perzon, Mattias; Gedeborg, Rolf; Blomqvist, Per; Johansson, Jakob (Högre utbildning, 2011)
The quality of clinical teaching in Swedish medical schools has recently been questioned by student representatives at the medical schools in Sweden. The clinical teaching at Uppsala University Medical School has previously only been sparsely evaluated and with varying instruments. Our aim was to develop a simple assessment instrument and implement it uniformly, enabling cross comparisons between different departments. Further we wanted to investigate students’ response rate and analyze their response pattern. A questionnaire inspired by a concept from Stanford University was created and introduced at hospital departments performing clinical teaching of medical students. Ten questions reflecting different aspects of clinical teaching were used. The outcome was used for specific feedback to the clinical teachers, cross comparison and official ranking of the departments. The evaluation instrument has been successfully developed and uniformly implemented throughout the departments of the hospital. The students have with a relatively high response rate graded the items with a great deal of variation between and within the clinical rotations. Altogether, this has provided specific feedback to the clinical teachers and enabled cross comparison between departments. Our belief is that the instrument also applies to other educations involving supervision.